HUBUNGAN HUBUNGAN FAKTOR DEMOGRAFI DAN KARAKTERISTIK DENGAN TINGKAT SPIRITUALITAS PELAYANAN GEREJA KRISTUS YESUS DI JAMBI - Subagio, Subagio; Tanadi, Lindawaty (STT Amanat Agung, 2024)
Background: The study of factors influencing the level of spirituality in the context of the church holds significant relevance in understanding the dynamics of the congregation's spiritual life. Gereja Kristus Yesus (GKY) in Jambi serves as an intriguing research site to explore the relationship between demographic factors and congregation characteristics with the level of spiritual service. This research aims to identify the relationship between demographic factors and congregation characteristics with the spiritual service level at GKY Jambi and provide deeper insights into the dynamics of spirituality within the church environment. Methods: This study employs a quantitative approach by collecting data through questionnaires distributed to members of the GKY Jambi congregation. The data were then analyzed using statistical techniques, including regression analysis and ANOVA, to evaluate the relationship between independent variables (demographic factors and congregation characteristics) and the dependent variable (level of spirituality). Results and Discussion: The analysis results indicate a significant relationship between certain demographic factors (such as age and education) and congregation characteristics (such as participation in worship) with the level of spiritual service. However, other factors, such as gender and marital status, did not show significant relationships. Conclusion: This study concludes that demographic factors (age) and congregation characteristics (participation in worship and duration of church involvement) can influence the level of spiritual service within the context of Gereja Kristus Yesus in Jambi. These findings provide a deeper understanding of the dynamics of spirituality in the local church environment and can serve as a basis for developing more effective and relevant ministry programs.Demographic Factors, Congregation Characteristics, Level of Spirituality